A composite material for strengthening microbial environment / modified nano-iron composite material and its preparation method and application
By preparing strengthened microbial environment/modified nanoferrous composites, the problem of difficult degradation of chlorine-containing volatile organic pollutants in groundwater is solved, rapid and persistent degradation effects are achieved, and the stability and reaction efficiency of nanoferrous are improved.
Patent Information
- Application Number
- CN202211610312.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The prior art is difficult to effectively degrade chlorine-containing volatile organic pollutants in groundwater, and nano-iron particles are prone to agglomeration and oxidation, and the degradation is not sustainable.
Using enhanced microbial environment/modified nanoferrous composite materials, the compound with capacity enhancement and improved nanoferrous reduction and suspension are prepared by mixing iron salt solutions, modifying metal material solutions and carrier materials, and adding reducing agents and enhancers. Material.
The rapid and persistent degradation of chlorine-containing volatile organic pollutants in groundwater has been achieved, the stability and reaction efficiency of nano-iron are improved, and secondary pollution is avoided.
Smart Images

Figure CN115925128B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental functional materials and environmental restoration, and relates to a composite material with adsorption, chemical reduction and microbial enhancement performance, and specifically relates to a composite material of microbial environment enhancement / modified nano-iron composite material, and a preparation method and application thereof. Background Art
[0002] Chlorinated Volatile Organic Compounds (CVOCs) are a type of VOCs, and common ones include chlorobenzene (PhCl), dichloromethane (DCM), dichloroethane (DCE), trichloromethane (TCM), trichloroethylene (TCE), carbon tetrachloride (CT), and tetrachloroethylene (TTCE). Chlorinated organic compounds mainly come from industrial production, such as trichloroethylene in the electronic semiconductor industry, dichloromethane, a widely used industrial solvent, and tetrachloroethylene frequently used in the dry cleaning industry. In the production of chlorinated hydrocarbons, there will be a large number of chlorinated hydrocarbon mixtures as waste by-products. For example, the waste liquid in the production of vinyl chloride contains low-boiling dichloroethane, chloroform, carbon tetrachloride, cis- and trans-dichloroethylene, which account for about 1.2% of the unit output of vinyl chloride. The high-boiling point by-product is mainly 1,1,2-trichloroethane, which accounts for 0.8% of the output of vinyl chloride. Chlorinated organic compounds are toxic, and some have been listed as carcinogens. Since the United States first reported that vinyl chloride can cause cancer in 1974, countries have imposed stricter regulations on the emission of chlorinated hydrocarbons. Among the 114 major pollutants identified by the U.S. Environmental Protection Agency, 61 are chlorinated hydrocarbon pollutants, including common chlorinated volatile organic compounds.
[0003] The chemical properties of most chlorinated organic compounds are relatively stable, and chlorine atoms are toxic to microorganisms. Therefore, they degrade slowly in nature and have a long environmental hazard cycle. For example, 1,2-dichloroethane is difficult to degrade after staying in the atmosphere for 5 months, and it can cause poisoning when inhaled by the human body. Chlorinated organic compounds are harmful to both the environment and the human body when discharged into the environment. Volatile chlorinated organic compounds have the ability to destroy the ozone layer, such as chlorofluorocarbons and chlorofluorocarbons. CVOCs in the air or steam enter the human blood through breathing to cause brain disorders, thereby inhibiting the central nervous system. When the concentration is high, headaches, dizziness, coughing, nausea, vomiting, etc. will occur. In severe cases, liver poisoning will occur, damaging the liver and nervous system, causing general weakness, drowsiness, skin itching, etc., and some may also cause endocrine disorders. Therefore, the development of a composite material for in-situ remediation of chlorinated volatile organic pollutants in groundwater can effectively reduce the pollution of organic matter in groundwater, reduce its diffusion into other environmental media, and thus enter the environment and human body, causing environmental damage and human damage.
[0004] Chlorinated volatile organic pollutants in groundwater are volatile, difficult to degrade and continuously released organic pollutants. They cannot be continuously and completely dechlorinated and degraded into harmless substances in the groundwater environment by a chemical degradation process. Therefore, it is necessary to develop a composite material that utilizes adsorption, chemical reduction and microbial reduction to dechlorinate and in situ remediate chlorinated volatile organic compounds in groundwater.
[0005] For toxic and harmful chlorinated organic matter, nano-iron is considered to be one of the most promising treatment technologies. This is because nano-iron particles have the ability to quickly degrade pollutants due to their small particle size, large specific surface area, high reactivity. Nano-iron particles have a stronger ability to treat pollutants because they have a very high specific surface area and surface activity compared to micron-sized particles. In addition, nano-iron can be suspended in water bodies well, and it can be directly injected into contaminated soil, sediment and water bodies for in-situ remediation. At the same time, nano-iron has achieved remarkable results in the treatment of difficult-to-degrade pollutants in the environment, such as chlorinated organic matter, heavy metal ions, and inorganic salt ions. However, nano-iron has the property of agglomeration, making it difficult to maintain a stable suspended state.
[0006] Nano iron particles all have a "shell structure" containing iron oxide or hydroxyl iron. This structure makes nano iron particles have both adsorption and chemical reduction properties. Due to the ultra-fine particle size of nano iron, large specific surface area, and high surface activity, nano particles are easily oxidized and even spontaneously combust. After oxidation, as the thickness of the formed oxide layer increases, the activity of the nano iron particles decreases, thereby affecting the treatment effect of pollutants. The specific surface area also has a great influence on the physical and chemical properties of the particles. In addition to factors such as particle size, core-shell structure, and particle composition, the reaction rate of nano-scale particles with pollutants will be greatly improved, so that the particles can effectively remove a variety of pollutants. At the same time, nano iron particles are aggregated in long chains due to their high specific surface area and magnetic field attraction, which reduces the particle reaction activity and reduces the migration ability in environmental remediation. Therefore, one direction for the research and development of this material is to prevent the aggregation of particles and improve the reaction efficiency by adding dispersants, carriers, etc.
[0007] Some scholars have studied the dechlorination and degradation of 6 kinds of vinyl chloride substances by nano-iron, and the results show that it can achieve a good degradation effect. According to research, the modification of nano-iron particles can enhance their stability and improve their reaction performance. Fe and other metals are prepared into bimetallic particles. The metal is a hydrogen storage metal. As a catalyst, it can enhance the treatment of pollutants, thereby accelerating the reaction rate of chlorine-containing compounds. In addition, the nano-iron particles are loaded and modified to increase their contact area with the target pollutants. At the same time, the highly active and fast-reacting nanoparticles are better dispersed, thereby preventing particle agglomeration and increasing their reaction rate. Therefore, whether it is to increase the loading material or use other metals as catalysts to prepare nano bimetallic particles, it can be used as a research and development direction to degrade chlorine-containing organic pollutants in groundwater.
[0008] The above is the research direction of modification based on the characteristics of nano iron particles themselves. Due to the characteristics of persistent release of chlorine-containing organic pollution in groundwater, it is necessary to improve the materials that take effect in the long term so that they can have a persistent effect. Therefore, in the above improvement direction, it is necessary to add materials that strengthen the microbial environment to the composite material to promote the liquid agent material to effectively and persistently repair chlorine-containing organic pollutants in groundwater. Summary of the invention
[0009] In view of the shortcomings of the prior art, the object of the present invention is to provide a composite material of a reinforced microbial environment / modified nano-iron composite material and its preparation method and application. The reinforced microbial environment / modified nano-iron composite material has a good degradation effect on organic pollutants in groundwater and can be used for in-situ remediation of chlorinated volatile organic pollutants in groundwater. It has a persistent effect on chlorinated volatile organic pollutants that are difficult to degrade and are continuously and slowly released into groundwater.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a method for preparing a microbial environment enhanced / modified nano-iron composite material, the preparation method comprising the following steps:
[0012] (1) mixing an iron salt solution, a modified metal material solution, and a carrier material, and uniformly mixing them to obtain a first mixed solution;
[0013] (2) under an inert gas atmosphere, adding a reducing agent solution to the first mixed solution obtained in step (1), and allowing the mixture to stand after the reaction to obtain a second mixed solution;
[0014] (3) The second mixed solution obtained in step (2) is treated anaerobicly, and then mixed with a reinforcing agent under an inert gas atmosphere, and oil-sealed to obtain the enhanced microbial environment / modified nano-iron composite material.
[0015] The present invention adopts a variety of environmental functional material preparation methods such as immersion method and surface chemical reduction method to prepare a composite material with the ability to increase the volume of organic pollutants in groundwater, improve the reducibility and suspension of nano-iron, and enhance the reduction and dechlorination ability of background microorganisms. Specifically, it utilizes the characteristics of nano-iron with ultra-fine particle size, large specific surface area, and high surface activity that can effectively degrade chlorinated organic pollutants. On this basis, the present invention modifies its shortcomings of easy agglomeration, easy oxidation, and weak degradation sustainability. In addition, by increasing the modification of carrier materials and modified metal materials, its dispersibility and adsorption are improved; by increasing surfactants, the volume increase and extraction of organic matter are improved; by increasing microbial strengthening materials, the sustained degradation effect of the reaction material is improved. The present invention combines various optimization directions to achieve rapid and sustained degradation and removal of chlorinated volatile organic pollutants in groundwater.
[0016] The enhanced microbial environment / modified nano-iron composite material provided by the present invention has a good degradation effect on organic pollutants in groundwater, and can be used for in-situ remediation of chlorinated volatile organic pollutants in groundwater. It has a persistent effect on chlorinated volatile organic pollutants that are difficult to degrade and are continuously and slowly released into groundwater.
[0017] As a preferred technical solution of the present invention, the iron salt solution in step (1) includes a trivalent iron salt solution or a divalent iron salt solution.
[0018] Preferably, the modified metal material solution in step (1) comprises a combination of at least two of any one of a nickel salt solution, a zinc salt solution, a copper salt solution, a silver salt solution or a gold salt solution. Typical but non-limiting combinations include a combination of a zinc salt solution and a copper salt solution, a combination of a nickel salt solution, a zinc salt solution, a copper salt solution and a silver salt solution, a combination of a copper salt solution, a silver salt solution and a gold salt solution, or a combination of a nickel salt solution, a zinc salt solution, a copper salt solution, a silver salt solution and a gold salt solution.
[0019] Preferably, the carrier material in step (1) comprises any one or a combination of at least two of biochar, montmorillonite, cellulose, chitosan or sodium dodecylbenzene sulfonate. Typical but non-limiting combinations include a combination of biochar and montmorillonite, a combination of biochar and cellulose, a combination of biochar and chitosan, or a combination of biochar, montmorillonite, cellulose and sodium dodecylbenzene sulfonate.
[0020] Preferably, the average particle size of the carrier material in step (1) is 80 to 300 mesh, for example, 80 mesh, 100 mesh, 150 mesh, 200 mesh, 250 mesh or 300 mesh, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; preferably 80 mesh.
[0021] Generally speaking, the larger the average particle size of the carrier material, the more conducive it is to the remediation treatment of the composite material and groundwater.
[0022] Preferably, the concentration ratio of the iron salt solution and the modified metal material solution in step (1) is (3-30):1, for example, it can be 3:1, 5:1, 10:1, 15:1, 20:1, 25:1 or 30:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] The concentration ratio of the iron salt solution to the modified metal material solution of the present invention is (3-30):1, wherein when the content of the modified metal material solution is too high, the cost is high and it is not conducive to industrial production; when it is too low, it will affect the effect of the composite material.
[0024] Preferably, the concentration ratio of the carrier material and the iron salt solution in step (1) is (1-9):1, for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or 9:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] The carrier material of the present invention is used to adsorb organic pollutants and reduce the overall concentration of pollutants; when its content is too high, the adsorption effect in the composite material plays a major role, the reduction effect will be weakened, and there will be a risk of pollutant precipitation in the later stage; if its content is too low, it cannot play the role of reducing the overall concentration atmosphere.
[0026] Preferably, the temperature of the uniform mixing in step (1) is 25-30°C, for example, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the uniform mixing time in step (1) is 10 to 60 min, for example, 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] The uniform mixing method of the present invention includes but is not limited to stirring.
[0029] Preferably, the reducing agent solution in step (2) comprises sodium borohydride solution and / or potassium borohydride solution.
[0030] The method for preparing the reducing agent solution of the present invention is: dissolving the reducing agent in oxygen-free deionized water in a closed environment. The reducing agent solution is prepared and stored in an oxygen-free environment in order to prevent the nano-iron in the iron salt solution from being oxidized.
[0031] Preferably, the molar ratio of the iron content in the reducing agent solution to the iron salt solution is (2-6):1, for example, it can be 2:1, 3:1, 4:1, 5:1 or 6:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] The reducing agent solution of the present invention is used to reduce iron salts to prepare zero-valent iron. Zero-valent iron reduces and dechlorinates to reduce the content of organic matter. If the content is too high, the production cost will increase, which is not conducive to industrial production. If the content is too low, it will not play the role of reducing iron salts to prepare zero-valent iron.
[0033] Preferably, the dropping speed in step (2) is 2 to 4 mL / min, for example, 2 mL / min, 2.4 mL / min, 2.8 mL / min, 3.2 mL / min, 3.6 mL / min or 4 mL / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] The dropwise addition speed of the present invention will affect the growth rate of the intermediates in the preparation process of the composite material. If it is too fast, the particle size of the intermediates produced will be too large, affecting the contact area of the materials. If it is too slow, it will take too long and will not be suitable for actual production.
[0035] Preferably, the reaction in step (2) comprises a stirring reaction.
[0036] Preferably, the stirring reaction time is 20 to 30 min, for example, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the enhancer in step (3) comprises a carbon source and / or an electron acceptor solution.
[0038] The carbon source described in the present invention is the carbon source required for strengthening microorganisms.
[0039] Preferably, the carbon source comprises any one of glucose, starch, saccharin or soybean oil or a combination of at least two thereof, typical but non-limiting combinations comprising a combination of glucose and starch, a combination of glucose and saccharin, a combination of glucose, starch, and saccharin, or a combination of glucose, starch, saccharin and soybean oil.
[0040] Preferably, the electron acceptor comprises any one of sodium acetate, ferrous sulfate or sodium bicarbonate or a combination of at least two thereof, typical but non-limiting combinations include a combination of sodium acetate and ferrous sulfate, a combination of sodium acetate and sodium bicarbonate, a combination of ferrous sulfate and sodium bicarbonate, or a combination of sodium acetate, ferrous sulfate and sodium bicarbonate.
[0041] Preferably, the mass ratio of the carbon source, the electron acceptor and the iron content in the iron salt solution of step (1) is (0.1-2):(0.1-1):1, for example, it can be 0.1:0.1:1, 0.5:0.1:1, 1:0.1:1, 0.1:0.5:1, 0.1:1:1 or 2:1:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] The preparation process of the enhancer in step (3) of the present invention is: dissolving the carbon source and / or the electron acceptor in oxygen-free deionized water to obtain a mixed solution of enhanced microorganisms (i.e., the enhancer). The enhancer needs to be isolated from oxygen during storage, and is generally isolated from oxygen by oil sealing.
[0043] The reinforcing agent (carbon source and / or electron acceptor solution) contained in the composite material of the present invention mainly plays a role of long-term sustained release. The long-term sustained release means that the reinforcing agent can slowly decompose and release the carbon source, which helps the composite material to stimulate microorganisms for a long time and is more conducive to the dechlorination and degradation of chlorinated hydrocarbons.
[0044] Preferably, the inert gas atmosphere in step (2) and step (3) includes a nitrogen gas atmosphere and / or an argon gas atmosphere.
[0045] Preferably, before the mixing in step (3), the process also includes extracting the supernatant of the second mixed liquid obtained in step (2).
[0046] The purpose of extracting the supernatant of the second mixed liquid in the present invention is to reduce the volume of the medicine and facilitate subsequent transportation; in addition, other interference factors can be reduced to facilitate the control of the amount of the composite material.
[0047] As a preferred technical solution of the present invention, the preparation method of the enhanced microbial environment / modified nano-iron composite material provided in the first aspect of the present invention comprises the following steps:
[0048] (1) mixing an iron salt solution, a modified metal material solution, and a carrier material, uniformly mixing at a temperature of 25 to 30° C. for 10 to 60 minutes to obtain a first mixed solution;
[0049] Wherein, the concentration ratio of the iron salt solution to the modified metal material solution is (3-30):1; the concentration ratio of the carrier material to the iron salt solution is (1-9):1;
[0050] (2) under an inert gas atmosphere, adding a reducing agent solution to the first mixed solution obtained in step (1) at a rate of 2 to 4 mL / min, stirring the mixture for 20 to 30 min, and then allowing the mixture to stand to obtain a second mixed solution;
[0051] The molar ratio of the iron content in the reducing agent solution to that in the iron salt solution is (2-6):1;
[0052] (3) dissolving the carbon source and / or electron acceptor required for the enhanced microorganisms in oxygen-free deionized water, and then mixing the second mixed solution after oxygen-free treatment under an inert gas atmosphere, and oil-sealing to obtain the enhanced microbial environment / modified nano-iron composite material;
[0053] The mass ratio of the carbon source, the electron acceptor and the iron content in the iron salt solution is (0.1-2):(0.1-1):1.
[0054] In a second aspect, the present invention provides an enhanced microbial environment / modified nano-iron composite material, wherein the enhanced microbial environment / modified nano-iron composite material is obtained by the preparation method provided in the first aspect.
[0055] In a third aspect, the present invention provides an application of an enhanced microbial environment / modified nano-iron composite material obtained by the preparation method provided in the first aspect, wherein the enhanced microbial environment / modified nano-iron composite material is used to treat organic pollutants in groundwater.
[0056] Preferably, the enhanced microbial environment / modified nano-iron composite material is used for in-situ remediation of groundwater contaminated by chlorinated volatile organic compounds.
[0057] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The enhanced microbial environment / modified nano-iron composite material provided by the present invention has high removal efficiency and fast removal rate for organic pollutants in groundwater, and has a good catalytic degradation effect on organic matter;
[0060] (2) The enhanced microbial environment / modified nano-iron composite material provided by the present invention can permanently degrade chlorine-containing volatile organic pollutants that enter groundwater without causing secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is an electron microscope scanning image of the enhanced microbial environment / modified nano-iron composite material provided in Example 1 of the present invention;
[0062] Figure 2 This is an electron microscope scanning image of the composite material provided in Comparative Example 1 of the present invention;
[0063] Figure 3This is an electron microscope scanning image of the composite material provided in Comparative Example 2 of the present invention;
[0064] Figure 4 This is an infrared analysis diagram of the composite material provided in Example 1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] Example 1
[0067] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material, and the preparation method of the microbial environment-enhanced / modified nano-iron composite material comprises the following steps:
[0068] (1) 4.324 g of FeSO4·7H2O, 1.293 g of Ni(NO3)2·6H2O and 2 g of ground and 200-mesh sieved biochar were dissolved in 30 ml of deionized water and stirred at 25°C for 30 min to obtain a first mixed solution;
[0069] (2) under nitrogen atmosphere, KBH4 solution was added dropwise at a rate of 3 mL / min to the first mixed solution obtained in step (1), stirred for reaction for 30 min, and then allowed to stand for 40 min, and then part of the supernatant was discarded to obtain a second mixed solution;
[0070] The preparation method of the KBH4 solution is as follows: weigh 3.24 g KBH4 and dissolve it in 60 ml of deoxygenated distilled water to prepare a 1.0 M KBH4 solution, wherein the second mixed solution has m KaBH4 :m FeSO4·7H2O =2.5:1;
[0071] (3) Weigh 2 g of glucose and 1 g of sodium acetate and dissolve them in 1 L of deionized water, mix them thoroughly and evenly, and then seal them with oil. Then, mix the second mixed solution obtained in step (2) under a nitrogen atmosphere, and seal them with oil to obtain the enhanced microbial environment / modified nano-iron composite material. The electron microscope scanning image of the enhanced microbial environment / modified nano-iron composite material is as follows: Figure 1 shown.
[0072] Example 2
[0073] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material, and the preparation method of the microbial environment-enhanced / modified nano-iron composite material comprises the following steps:
[0074] (1) 4.324 g of FeSO4·7H2O, 0.6465 g of Ni(NO3)2·6H2O and 2 g of ground and 200-mesh sieved biochar were dissolved in 30 ml of deionized water and stirred at 25°C for 30 min to obtain a first mixed solution;
[0075] (2) under nitrogen atmosphere, KBH4 solution was added dropwise at a rate of 3 mL / min to the first mixed solution obtained in step (1), stirred for reaction for 30 min, and then allowed to stand for 40 min, and then part of the supernatant was discarded to obtain a second mixed solution;
[0076] The preparation method of the KBH4 solution is as follows: weigh 3.24 g KBH4 and dissolve it in 60 ml of deoxygenated distilled water to prepare a 1.0 M KBH4 solution, wherein the second mixed solution has m KaBH4 :m FeSO4·7H2O =3:1;
[0077] (3) Weigh 2 g of glucose and 1 g of sodium acetate and dissolve them in 1 L of deionized water. Mix them thoroughly and then seal them with oil. Then, mix the second mixed solution obtained in step (2) under a nitrogen atmosphere and seal them with oil to obtain the enhanced microbial environment / modified nano-iron composite material.
[0078] Example 3
[0079] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material. The preparation method of the microbial environment-enhanced / modified nano-iron composite material is different from that of Embodiment 1 only in that:
[0080] In this example, the carrier material described in step (1) is changed to 2 g of biochar that has been ground and passed through a 200-mesh sieve and 2 g of sodium dodecylbenzene cyclopentane.
[0081] Compared with Example 1, this example adds a carrier sodium dodecylbenzene sulfonate during the preparation process, which can increase the solubility of organic pollutants while promoting the dispersion of nano-iron materials, adsorb organic pollutants through supercritical micelles, and enhance the removal of organic pollutants.
[0082] Example 4
[0083] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material. The preparation method of the microbial environment-enhanced / modified nano-iron composite material is different from that of Embodiment 1 only in that:
[0084] In this example, the 2 g of glucose and 1 g of sodium acetate in step (3) are changed to “2 g of saccharin and 1 g of sodium lactate”.
[0085] Example 5
[0086] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material. The preparation method of the microbial environment-enhanced / modified nano-iron composite material is different from that of Embodiment 1 only in that:
[0087] In this embodiment, the m NaBH4 :m FeSO4·6H2O The ratio is changed to 1:1.
[0088] Example 6
[0089] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material. The preparation method of the microbial environment-enhanced / modified nano-iron composite material is different from that of Embodiment 1 only in that:
[0090] In this embodiment, step (2) is NaBH4 :m FeSO4·6H2O The ratio is changed to 4:1.
[0091] Example 7
[0092] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material. The preparation method of the microbial environment-enhanced / modified nano-iron composite material is different from that of Embodiment 1 only in that:
[0093] In this embodiment, the sodium acetate in step (3) is replaced with starch of the same mass, that is, the electron acceptor solution is omitted in this embodiment.
[0094] Example 8
[0095] This embodiment provides a microbial environment-enhanced / modified nano-iron composite material. The preparation method of the microbial environment-enhanced / modified nano-iron composite material is different from that of Embodiment 1 only in that:
[0096] In this embodiment, the glucose in step (3) is replaced with a sodium bicarbonate solution of the same mass, that is, the carbon source is omitted in this embodiment.
[0097] Comparative Example 1
[0098] This comparative example provides a composite material, and the preparation method of the composite material is different from that of Example 1 only in that:
[0099] In this comparative example, Ni(NO3)2·6H2O described in step (1) was omitted.
[0100] The electron microscope scanning image of the composite material provided in this comparative example is as follows Figure 2 shown.
[0101] Comparative Example 2
[0102] This comparative example provides a composite material, and the preparation method of the composite material is different from that of Example 1 only in that:
[0103] In this comparative example, Ni(NO3)2·6H2O and biochar described in step (1) were omitted.
[0104] The electron microscope scanning image of the composite material provided in this comparative example is as follows Figure 3 shown.
[0105] Comparative Example 3
[0106] This comparative example provides a composite material, and the preparation method of the composite material is different from that of Example 1 only in that:
[0107] In this comparative example, the biochar described in step (1) was omitted.
[0108] Comparative Example 4
[0109] This comparative example provides a composite material, and the preparation method of the composite material is different from that of Example 1 only in that:
[0110] In this comparative example, step (3) is omitted, that is, there is no reinforcing agent in the composite material provided in this comparative example.
[0111] The composite materials provided in Examples 1-8 and Comparative Examples 1-4 were injected in situ into the contaminated groundwater area to degrade chlorinated volatile organic pollutants such as 1,2-dichloroethane. The degradation effects are shown in Tables 1 and 2.
[0112] Table 1
[0113]
[0114]
[0115] Considering factors such as actual engineering costs, it can be seen from Table 1 that the composite material provided by the present invention has the best degradation effect on contaminated groundwater when the addition ratio is 3%. Therefore, with respect to the test results of the degradation effect of the composite material provided by the present invention on contaminated groundwater, the present invention only provides the degradation effect of the composite materials provided by Examples 2-8 and Comparative Examples 1-4 when the addition ratio is 3% (as shown in Table 2) to truly reflect the advantage of the degradation effect of the composite material provided by the present invention on contaminated groundwater.
[0116] Table 2
[0117]
[0118]
[0119]
[0120] The blank control described in Table 1 is: 1,2-dichloroethane pollution data of contaminated water samples collected in situ from groundwater at actual 1,2-dichloroethane contaminated sites.
[0121] As shown in Table 2, within 7 days, adsorption plays a major role in the degradation of chlorinated hydrocarbon 1,2-dichloroethane, and reduction and microbial action play a minor role. However, after 30 days of subsequent reaction, Example 1 can degrade 1,2-dichloroethane to 24.5661ug / L. As the reaction proceeds, the microbial degradation of indigenous microorganisms in the actual water sample plays a major role. However, the reaction time of this action is relatively long and requires long-term detection. Reducing the concentration of pollutants through adsorption and reduction in the early stage is more conducive to the biodegradation of microorganisms in the later stage. This material can achieve long-term effectiveness through microbial action.
[0122] The composite materials provided in Example 1 and Comparative Examples 1-3 of the present invention were subjected to infrared detection (such as Figure 4 As shown in Figure 2, it can be concluded that in the absence of a carrier material, zero-valent iron and zero-valent iron-nickel are easily oxidized and the Fe-O peak is high, 1000 cm -1 There are more peaks of the metal oxides below, so it can be seen that the support material has a better protective effect on the zero-valent iron that plays a reducing role.
[0123] In summary, the enhanced microbial environment / modified nano-iron composite material provided by the present invention has a good degradation effect on organic pollutants in groundwater, and can be used for in-situ remediation of chlorinated volatile organic pollutants in groundwater. It has a persistent effect on chlorinated volatile organic pollutants that are difficult to degrade and are continuously and slowly released into groundwater.
[0124] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0125] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a microbial environment-enhanced / modified nano-iron composite material, characterized in that: The preparation method comprises the following steps: (1) mixing an iron salt solution, a modified metal material solution, and a carrier material, and uniformly mixing them to obtain a first mixed solution; (2) under an inert gas atmosphere, adding a reducing agent solution to the first mixed solution obtained in step (1), and allowing the mixture to stand after the reaction to obtain a second mixed solution; (3) treating the second mixed solution obtained in step (2) in anoxic condition, and then mixing the enhancer under an inert gas atmosphere, and oil-sealing to obtain the enhanced microbial environment / modified nano-iron composite material; the enhancer includes a carbon source and / or an electron acceptor solution; The modified metal material solution in step (1) comprises a combination of at least two of any one of a nickel salt solution, a zinc salt solution, a copper salt solution, a silver salt solution or a gold salt solution; The carrier material in step (1) includes any one of biochar, montmorillonite, cellulose, chitosan or sodium dodecylbenzene sulfonate, or a combination of at least two thereof.
2. The preparation method according to claim 1, characterized in that: The iron salt solution in step (1) includes a ferric salt solution or a ferrous salt solution.
3. The preparation method according to claim 1, characterized in that: The concentration ratio of the iron salt solution and the modified metal material solution in step (1) is (3-30):
1.
4. The preparation method according to claim 1, characterized in that: The concentration ratio of the carrier material and the iron salt solution in step (1) is (1-9):
1.
5. The preparation method according to claim 1, characterized in that: The temperature of the uniform mixing in step (1) is 25-30°C.
6. The preparation method according to claim 1, characterized in that: The uniform mixing time in step (1) is 10 to 60 minutes.
7. The preparation method according to claim 1, characterized in that: The reducing agent solution in step (2) includes sodium borohydride solution and / or potassium borohydride solution.
8. The preparation method according to claim 1, characterized in that: The molar ratio of the iron content in the reducing agent solution to that in the iron salt solution is (2-6):
1.
9. The preparation method according to claim 1, characterized in that: The dropping speed in step (2) is 2 to 4 mL / min.
10. The preparation method according to claim 1, characterized in that: The reaction in step (2) comprises a stirring reaction.
11. The preparation method according to claim 10, characterized in that: The stirring reaction time is 20 to 30 minutes.
12. The preparation method according to claim 1, characterized in that: The carbon source includes any one of glucose, starch, saccharin or soybean oil, or a combination of at least two of them.
13. The preparation method according to claim 1, characterized in that: The electron acceptor solution includes any one of sodium acetate, ferrous sulfate or sodium bicarbonate, or a combination of at least two of them.
14. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon source, the electron acceptor and the iron content in the iron salt solution is (0.1-2):(0.1-1):
1.
15. The preparation method according to claim 1, characterized in that: The inert gas atmosphere in step (2) and step (3) includes a nitrogen gas atmosphere and / or an argon gas atmosphere.
16. The preparation method according to claim 1, characterized in that: Before the mixing in step (3), the process of extracting the supernatant of the second mixed solution obtained in step (2) is also included.
17. A microbial environment enhanced / modified nano-iron composite material, characterized in that: The enhanced microbial environment / modified nano-iron composite material is obtained by the preparation method provided in any one of claims 1-16.
18. An application of the microbial environment enhanced / modified nano-iron composite material as claimed in claim 17, characterized in that: The enhanced microbial environment / modified nano-iron composite material is used for treating organic pollutants in groundwater.
19. The use according to claim 18, characterized in that The enhanced microbial environment / modified nano-iron composite material is used for in-situ remediation of groundwater contaminated by chlorinated volatile organic matter.
Citation Information
Patent Citations
Slow-release compound repair material for treating chlorine-containing organic pollutants in groundwater and preparation method thereof
CN104944568A
Superparamagnetic nano-iron material and composite material, preparation method and application thereof
CN115106519A